1993
DOI: 10.3354/meps095141
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis-irradiance relationships and production associated with a warm-core ring shed from the Agulhas Retroflection south of Africa

Abstract: Synoptic estimates of phytoplankton biomass and production in the world's oceans are dependent upon ocean colour remote sensing and suitable algorithms developed from simultaneous measurements of photosynthetic parameters and optical properties in the water column. This study presents Photosynthesis-Irradiance (P-I) parameters estimated for a warm-core ring shed from the Agulhas Retroflection, in autumn, in the region of the Sub-Tropical Convergence south of Africa. Comparisons are made between values within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 31 publications
3
13
0
Order By: Relevance
“…Decreasing P B m POC is frequently associated with increasing α (e.g. Dower & Lucas 1993, Basterretxea & Arístegui 2000, Morán et al 2001, whereas both parameters decreased similarly with depth in our experiments (Fig. 5).…”
Section: Photosynthetic Parameterssupporting
confidence: 59%
See 1 more Smart Citation
“…Decreasing P B m POC is frequently associated with increasing α (e.g. Dower & Lucas 1993, Basterretxea & Arístegui 2000, Morán et al 2001, whereas both parameters decreased similarly with depth in our experiments (Fig. 5).…”
Section: Photosynthetic Parameterssupporting
confidence: 59%
“…2, using interpolation of photosynthetic parameters at each depth, as more appropriate than just taking 2 sets of constant values changed at a given depth of the water column. Apart from the observation that Z uml was shallower than the depth of the most superficial sample at Stns C2, A3 and B3 (Table 1), the fact that P-E parameters also varied with depth within the upper mixed layer, argued against the use of the uppermost values throughout all the upper mixed layer (Dower & Lucas 1993).…”
Section: Integrated Primary Productionmentioning
confidence: 99%
“…Whether these were mesoscale eddies, filaments, or larger frontal structures, is not possible to determine from a single section, however such structures have been observed previously (Read and Pollard, 1993) and attributed to eddies (e.g., Pollard and Regier, 1992). Such eddies would result in substantial heat loss and convective overturning that entrains nutrients into surface waters (Dower and Lucas, 1993;Pollard et al, 2002), with the potential to enhance primary production wherever stability and stratification occurs. Despite high NO 3 concentrations (104-1074 mmol m −2 ), primary production is still based primarily on regenerated nutrients as revealed by low f-ratios (< 0.5) (Fig.…”
Section: Chlorophyll Distribution and N Assimilation South Of The Stfmentioning
confidence: 99%
“…It has recently been demonstrated that eddies spawned off the major frontal systems are rich in zooplankton/micronekton standing stock (Craddock et al 1992, Wiebe & Youce 1992, Pakhomov et al 1994, Pakhomov & Perissinotto 1997. The eddies may persist for up to 6 mo (Lutjeharms & Gordon 1987, Lutjeharms & Valentine 1988 and exhibited elevated primary productivity at the edges (Dower & Lucas 1993, Froneman et al 1999. Eddies are therefore regarded as important vehicles in transporting unique or dense zooplankton communities, providing ideal feeding grounds for top predators (Sugimoto & Tameishi 1992, Barange et al 1998).…”
Section: Prey Items Associated With Particular Oceanographic Featuresmentioning
confidence: 99%